Mobile tracking system and optical tracking integration for mobile mixed reality. (2016) - Bajana, JÁ¡n; Francia, Daniela; Liverani, Alfredo; KrajÄoviÄ, Martin
Augmented Reality (AR) technology is becoming more available for everyday applications, providing advanced information about the observed objects. In this paper we present a system combining optical tracking and augmented reality with applications in local large areas. We use two different tracking technologies for positioning objects: the infrared marker-based motion capture system OptiTrack and the Vuforia software platform, which enables augmented reality app across the real world environment. We present a robust solution for communication between a client (mobile platform) and a server that computes all global tracking data. This technology has high potential for end users and can be of great benefit.